2000
DOI: 10.1034/j.1600-0684.2000.290304.x
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and characterization of a highly pathogenic isolate of human immunodeficiency virus type 2 that causes rapid CD4+ cell depletion in Macaca nemestrina

Abstract: With few exceptions, humans are the only species known to develop acquired immunodeficiency syndrome (AIDS) after human immunodeficiency virus (HIV) infection. We report here that an isolate of HIV type 2, EHO, readily established persistent infection in 100% of Macaca nemestrina in three consecutive transmission studies. Of the eight infected animals, five showed persistently high virus load and six developed AIDS-like diseases or CD4+ cell depletion within 4 years of infection. The pathology and clinical sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…The lymph node pathology in HIV-2-infected animals was similar to that seen in some HIV-2-infected macaques and in HIV-1-infected humans (4,11,12,32,34,35) and was most progressive after the third serial passage (i.e., baboons 11966, 12741, and 12933). In addition, the uneven distribution of follicular dendritic cell-bound HIV is also often seen in cases of HIV-1 infection.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The lymph node pathology in HIV-2-infected animals was similar to that seen in some HIV-2-infected macaques and in HIV-1-infected humans (4,11,12,32,34,35) and was most progressive after the third serial passage (i.e., baboons 11966, 12741, and 12933). In addition, the uneven distribution of follicular dendritic cell-bound HIV is also often seen in cases of HIV-1 infection.…”
Section: Discussionmentioning
confidence: 61%
“…HIV-1 and HIV-2 isolates have been inoculated into several nonhuman primates (1,11,18,33,40), but with HIV-2, only baboons (Papio cynocephalus) and pig-tailed macaques develop an AIDS-like disease (3,28,31,32). The infection course in baboons resembles the slow, lentiviral disease progression that is observed in chronic HIV-1 infection in humans.…”
mentioning
confidence: 99%
“…Our laboratory has shown that Macaca nemestrina animals are susceptible to infection with a primary HIV-2 isolate, HIV-2/EHO (14,25). M. nemestrina macaques have also been reported to be susceptible to some HIV-1 isolates (1,(4)(5)(6)(7)19) although this idea remains controversial.…”
mentioning
confidence: 90%
“…Importantly, in contrast to other nonhuman primate models, PTM are susceptible to many lentiviral infections other than SIV and SHIV, including infection with HIV-1, HIV-2, and simian tropic (stHIV-1) (1,3,6,24,29,42,49,55,60), which makes this model invaluable for vaccination and pathogenesis studies. Furthermore, recent characterization of APOBEC and TRIM5␣ genes in PTM has allowed for the development of minimally chimeric stHIV-1 strains, differing from HIV-1 only in vif genes, that persistently infect PTM due to the TRIMCyp fusion protein which PTM harbor rather than TRIM5 (11,21,60).…”
mentioning
confidence: 99%